AB0025 Mtor pathway activation in large vessel vasculitis. (12th June 2018) - Comarmond, C.; Maciejewski-Duval, A.; Leroyer, A.; Zaidan, M.; Le Joncour, A.; Cacoub, P.; Sadoun, D.
Abstract : Background: Mammalian target of rapamycin complex 1 (mTORC 1) drives the proinflammatory expansion of T helper (TH) type 1, TH17 cells and controls fibroblast proliferation, typical features of large vessel vasculitis (LVV) pathogenesis. Molecular pathways involved in arterial lesions of LVV are unknown. Objectives: To analyse mTOR pathway activation in LVV (giant cell arteritis and Takayasu arteritis). Methods: We evaluate pathway activation in the mTORC and the nature of cell proliferation in blood and vessels of patients with LVV compared non-inflammatory aorta by using double immunostaining, western blot and flow cytometry. Finally, using flow cytometry, we study the effect of rapamycin on T cells homeostasis in LVV compared to HD. Results: Proliferation of both endothelial cells and vascular smooth-muscle cells was shown in vascular lesions in LVV. The vascular endothelium of proliferating aorta vessels from patients with LVV showed indications of activation of the mTORC1 pathway en endothelial cells (S6RP phosphorylation) compared to non-inflammatory aorta (45% 24;48 versus 10.4% [9.7;14.9] positive S6RP endothelial cells, p=0.03). In cultured vascular endothelial cells, sera from patients with LVV stimulated mTORC1 through the phosphorylation of S6RP. Activation of mTORC1 was also found in Th1 and Th17 cells both systemically and in the blood vessels. Patients with LVV exhibited a diminished S6RP phosphorylation in Tregs. Inhibition of mTORC1 pathway with rapamycin, increase Tregs and decrease effector CD4 + IFNγ +, CD4 + IL17 + and CD4 + IL21 + T cells in patients with LVV. Conclusions: Our results suggest that the mTORC1 pathway is involved in the vascular lesions of LVV. Targeting mTORC pathway may represent a new therapeutic option in patients with LVV. Disclosure of Interest: None declared